The Evolution and Legacy of Ghazni: Tracing Its Historical and Cultural Impact from Antiquity to the Zenith of the Islamic Golden Age - Wafiullah Aminzai; Habibullah Haidari; Ziauddin Hotak (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The Evolution and Legacy of Ghazni Tracing Its Historical and Cultural Impact from Antiquity to the Zenith of the Islamic Golden Age, delves into the multifaceted role of Ghazni as a central hub of cultural, political, and intellectual exchange across centuries. Situated at the crossroads of ancient trade routes, Ghazni emerged as a vital link between diverse civilizations, evolving from an ancient settlement to a flourishing center during the Islamic Golden Age. The primary objective of this research is to examine Ghazni’s socio-political, economic, and cultural transformations, with a particular focus on its contributions to art, architecture, literature, and governance. By doing so, the study aims to illuminate how Ghazni became a beacon of knowledge and creativity, influencing the broader Islamic world and beyond. The need for this research stems from the critical role Ghazni played in shaping regional and global history, yet its legacy remains underexplored in contemporary scholarship. Employing a library research methodology, the study synthesizes historical texts, archaeological evidence, and scholarly analyses to reconstruct Ghazni’s historical trajectory. Key findings reveal Ghazni’s strategic importance as a trade and cultural nexus, its role in fostering intellectual and artistic exchanges, and its enduring impact on Islamic civilization. The research underscores Ghazni’s significance as a center of learning and cultural production, highlighting its contributions to the preservation and dissemination of knowledge during the Islamic Golden Age. Ultimately, this study provides a comprehensive understanding of Ghazni’s historical and cultural legacy, offering valuable insights into its role as a bridge between antiquity and the zenith of Islamic civilization.